Onset of action and duration of efficacy of inferior alveolar nerve block versus single lingual subperi-osteal injection of 4% articaine in mandibular second molars: A randomized clinical trial - E Esnaashari; SH Mirzaei; AA Moshari; P Razavi (Islamic Azad University, 2022)
Background and Aim: Achieving adequate pulpal anesthesia could be challenging in mandibular molars. There are some disagreements about the success rate of local infiltration anesthesia with articaine as primary injection. Therefore, the aim of this study was to assess the efficacy of 4% articaine lingual subperiosteal injection as the primary injection for permanent mandibular second molars in comparison with inferior alveolar nerve block (IANB).   Materials and Methods: Fifteen healthy adult volunteers participated in this study. A randomized, split-mouth, single-blind design was used to allocate each side of the mandible in each patient to the test or control group. On the test side, lingual subperiosteal injection with 4% articaine and 1:100,000 epinephrine was performed for the mandibular second molar; whereas, in the control group, an IANB with 2% lidocaine and 1:80,000 epinephrine was administered. Electric pulp testing was done at baseline, and also at 5, 8, 11, 15, 20, 25, 30, 45, 60, 75, and 90 minutes after injection. Statistical analysis was carried out using t-test and Chi-square test. Results: The success rate of IANB was significantly higher than that of lingual subperiosteal injection (P=0.0001). The difference in the onset of action between the two groups was significant (P<0.05). Anesthesia duration was 61.0±28.0 minutes in IANB group and 10.2±12.4 minutes in lingual subperiosteal injection group, with a significant difference between them (P<0.01). Conclusion: IANB with 2% lidocaine is preferable to 4% articaine lingual subperiosteal injection due to its superior success rate, faster onset of action, and longer duration of effect.